A brief report on the effects of vasoactive agents on peripheral venous waveforms in a porcine model. (July 2020) - Polcz, Monica; Hocking, Kyle M; Chang, Devin; Leisy, Philip; Sobey, Jenna H; Huston, Jessica; Eagle, Susan; Brophy, Colleen; Alvis, Bret D
Objectives: Non-invasive venous waveform analysis (NIVA) is a recently described, novel technique to assess intravascular volume status. Waveforms are captured with a piezoelectric sensor; analysis in the frequency domain allows for calculation of a "NIVA value" that represents volume status. The aim of this report was to determine the effects of vasoactive agents on the venous waveform and calculated NIVA values. Design: Porcine experimental model. Setting: Operating theatre. Participants: A piezoelectric sensor was secured over the surgically exposed saphenous vein in eight anesthetized pigs. Main outcome measures: NIVA value, pulmonary capillary wedge pressure (PCWP), and mean arterial pressure prior to and post intravenous administration of 150–180 µg of phenylephrine or 100 µg of sodium nitroprusside. Results: Phenylephrine led to a decrease in NIVA value (mean 9.2 vs. 4.6, p < 0.05), while sodium nitroprusside led to an increase in NIVA value (mean 9.5 vs. 11.9, p < 0.05). Mean arterial pressure increased after phenylephrine ( p < 0.05) and decreased after sodium nitroprusside ( p < 0.05). PCWP did not change significantly after phenylephrine ( p = 0.25) or sodium nitroprusside ( p = 0.06). Conclusions: Vasoactive agents lead to changes in non-invasively obtained venous waveforms in euvolemic pigs, highlighting a potential limitation in the ability to NIVA to estimate static volume in this setting. Further studies are indicated to understand the effects of vasoactive agents in the setting of hypovolemia and hypervolemia.